ANALISIS PERKEMBANGAN SISTEM PERADILAN PIDANA DITINJAU DARI PERSPEKTIF PENGADILAN TINDAK PIDANA KORUPSI - .Fitriati, Fitriati (Faculty of Law, Universitas Sebelas Maret, 2014)
Under Law No. 30 Year 2002 on Corruption Eradication Commission , in particular in Article 53 . Corruption Court is located in the General Court . Initially he was not formed by a special law or its own but one package with the establishment of the Corruption Eradication Commission ( KPK ). Key developments other Corruption Court is authorized as provided in Article 6 of Law No. 46 of 2009 , which states that the Anti-Corruption Court has authority to examine , hear and decide the case : corruption , money laundering is the underlying predicate offenses of corruption and criminal offenses expressly provided in other laws defined as corruption . In addition, the trial of corruption in the region . Eradication of corruption is a systematic and continuous one can do with efforts to establish court corruption ( corruption ) which is located in every capital city / town in Indonesia . Problems of development of the criminal justice system in Indonesia in terms of authority corruption court is a court of corruption that is in the many different areas acquittal of corruption cases .